2022
DOI: 10.1021/acs.orglett.2c02042
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Deaminative Allenylation of Amino Acid Derivatives: Catalytic Activity Enhanced by an Amide-Type NN2 Pincer Ligand

Abstract: Herein, we report a general and practical nickel-catalyzed deaminative allenylation of amino acid derivatives with terminal alkynes. The well-designed, electron deficient, and sterically hindered amide-type NN 2 pincer ligand was crucial to the success of this transformation, enabling the coupling to occur under mild conditions with high efficiency. The remarkable features of this chemistry are its good scalability, its broad substrate scope, functional group tolerance, and the efficient modification of peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In 2022, Zhang and co‐workers developed an elegant nickel‐catalyzed deaminative allenylation of amino acid‐derived pyridinium salts with terminal alkynes for the expedient synthesis of allene derivatives (Scheme 26). [54] The key to the success of this transformation was the development of a new, electron‐deficient, and sterically hindered amide‐type NN 2 pincer ligand, [55] which enabled the reaction to proceed under mild conditions with high efficiency. A broad range of terminal alkynes and pyridinium salts containing various functional groups such as halide, ester, ether, free hydroxy, amino, acetyl, acetal, and cyano were well‐accommodated, delivering the target allene products in good to excellent yields.…”
Section: Nickel‐catalyzed Synthesis Of Allenes Via Radical Pathwaysmentioning
confidence: 99%
“…In 2022, Zhang and co‐workers developed an elegant nickel‐catalyzed deaminative allenylation of amino acid‐derived pyridinium salts with terminal alkynes for the expedient synthesis of allene derivatives (Scheme 26). [54] The key to the success of this transformation was the development of a new, electron‐deficient, and sterically hindered amide‐type NN 2 pincer ligand, [55] which enabled the reaction to proceed under mild conditions with high efficiency. A broad range of terminal alkynes and pyridinium salts containing various functional groups such as halide, ester, ether, free hydroxy, amino, acetyl, acetal, and cyano were well‐accommodated, delivering the target allene products in good to excellent yields.…”
Section: Nickel‐catalyzed Synthesis Of Allenes Via Radical Pathwaysmentioning
confidence: 99%
“…However, to the best of our knowledge, such an appealing approach has not been developed. During our investigation on nickel-catalyzed cross-coupling with pyridinium salts, 16 we serendipitously discovered that an important azepine product was generated in the reaction mixture when a pyridinium salt derived from phenylalanine was utilized. Considering the significant role of azepine moieties in bioactive molecules, we herein disclose a mild and practical method for the synthesis of these valuable scaffolds from amino acid derivatives with high efficiency (Scheme 1 grey box).…”
Section: Introductionmentioning
confidence: 99%
“…The mass balance for this reaction was ascribed to the generation of some inevitable byproducts such as ketone (from imine hydrolysis) and hydrogenated pyrroline (from reductive cyclization). Ligand screening indicated that the tridentate nitrogen-based ligands (e.g., L1 – L3 ), which gave the best results in our nickel-catalyzed alkynylation reactions, , were inferior for this transformation, while the bidentate ones (e.g., L4 – L6 ) delivered superior performance; the relatively electron-rich L6 remained the optimal ligand (entries 2–6). Other nickel sources, including NiCl 2 (glyme), NiI 2 , and Ni­(acac) 2 , were also effective precatalysts for this iminoarylation process, albeit with reduced yields (entries 7–9, respectively).…”
mentioning
confidence: 99%
“…With our continued interest in developing novel transformations by nickel catalysis and recent work on iminoalkynylation of unsaturated oxime esters with terminal alkynes, herein, we disclose the first example of nickel-catalyzed iminoarylation of oxime ester-tethered alkenes with (hetero)­aryl halides via a reductive strategy (Scheme B). This transformation features mild conditions, a broad substrate scope, excellent functional group tolerance, and efficient late-stage modification of several drug derivatives.…”
mentioning
confidence: 99%